Application of Photoperiod Manipulation and Type of Feed on the Growth and Survival of Clarias gariepinus Fry - Pandiangan, Dian Pramanda; Suharman, Indra; Aryani, Netti (Jurnal Perikanan dan Kelautan, 2023)
African catfish (Clarias gariepinus) is a freshwater fish that has the advantages of fast growth, high economic value, adaptability to environmental changes, and easy marketing. This study aims to analyze the growth rate, survival rate, and nutritional content of African catfish after being treated with photoperiod and different types of feed. The research was conducted from September to December 2022, at the Fish Health Laboratory at the Matauli Marine and Fishery College, Central Tapanuli. The method used is an experimental method by applying a Completely Randomized Design Factorial, two factors, and three replications. The first factor is the photoperiod (B), namely natural (B1), 18 hours dark 6 hours light (B2), 24 hours dark (B3), and the second factor is the type of feed (A), commercial feed (A1) and maggot (A2). The test fish used were obtained from the Central Tapanuli Fish Cultivation Seed Center measuring 16.01±0.02 cm and weighing 30.00 ± 0.00 g for a total of 126 individuals. Fish were reared for four weeks in rearing containers with a stocking density of 1 fish/10L. Feed is given four times a day, namely at 06.00, 12.00, 18.00, and 24.00 ad satiation. The results showed that photoperiod manipulation and different types of feed affected the growth and survival of African catfish fry (p<0.05). The combination of photoperiod 24 hours dark and maggot feed (B3A2) gave the best results on absolute weight growth of 22.70g, absolute length of 2.56 cm, a specific growth rate of 2.01%/day, a survival rate of 100%, and nutritional content of fish meat such as protein of 18.97%, 8.68% fat, 0.73% fiber, 1.54% ash, and 80.26% water